Injecting hope: the potential of intratumoral immunotherapy for locally advanced and metastatic cancer - Skalickova, Marketa; Hadrava Vanova, Katerina; Uher, Ondrej; Leischner Fialova, Jindriska; Petrlakova, Katerina; Masarik, Michal; Kejík, Zdeněk; Martasek, Pavel; Pacak, Karel; Jakubek, Milan (Frontiers in Immunology, 2025)
Despite enormous progress, advanced cancers are still one of the most serious medical problems in current society. Although various agents and therapeutic strategies with anticancer activity are known and used, they often fail to achieve satisfactory long-term patient outcomes and survival. Recently, immunotherapy has shown success in patients by harnessing important interactions between the immune system and cancer. However, many of these therapies lead to frequent side effects when administered systemically, prompting treatment modifications or discontinuation or, in severe cases, fatalities. New therapeutic approaches like intratumoral immunotherapy, characterized by reduced side effects, cost, and systemic toxicity, offer promising prospects for future applications in clinical oncology. In the context of locally advanced or metastatic cancer, combining diverse immunotherapeutic and other treatment strategies targeting multiple cancer hallmarks appears crucial. Such combination therapies hold promise for improving patient outcomes and survival and for promoting a sustained systemic response. This review aims to provide a current overview of immunotherapeutic approaches, specifically focusing on the intratumoral administration of drugs in patients with locally advanced and metastatic cancers. It also explores the integration of intratumoral administration with other modalities to maximize therapeutic response. Additionally, the review summarizes recent advances in intratumoral immunotherapy and discusses novel therapeutic approaches, outlining future directions in the field.